1986
DOI: 10.1210/endo-118-6-2577
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Insulin Action in Cultured Pig Adipose Tissue by Pituitary and Recombinant Porcine Growth Hormone: Potentiation by Hydrocortisone*

Abstract: The effects of physiological levels of pituitary porcine GH (ppGH) and recombinant pGH (rpGH) on lipogenesis in pig adipose tissue incubated with insulin and hydrocortisone (HC) were measured in short term (2-h) incubations and after long term culture (50 h). HC (50 ng/ml) had no effect on lipogenesis in 2-h incubations; however, HC and insulin (10 ng/ml) maintained the lipogenic capacity of cultured tissue at rates comparable to those in fresh adipose tissue. Neither ppGH nor rpGH (1 and 10 ng/ml, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…Studies with cell lines have shown that hypoxic conditions increased both the rate of glycolysis and the activity of glycolytic enzymes, including pyruvate kinase (Robin et al, 1984;Ptashne et al, 1985). Antimycin A in the present study also appeared to increase glycolysis, as evidenced by the increase in glucose uptake and lactate output in its presence, but failed to increase pyruvate kinase activity (at (Vernon, 1982;Vernon et al, 1985;Etherton & Evock, 1986 (Livingston & Moxley, 1982;James et al, 1985), but the mechanism is unknown.…”
Section: Pyruvate Kinasecontrasting
confidence: 45%
See 1 more Smart Citation
“…Studies with cell lines have shown that hypoxic conditions increased both the rate of glycolysis and the activity of glycolytic enzymes, including pyruvate kinase (Robin et al, 1984;Ptashne et al, 1985). Antimycin A in the present study also appeared to increase glycolysis, as evidenced by the increase in glucose uptake and lactate output in its presence, but failed to increase pyruvate kinase activity (at (Vernon, 1982;Vernon et al, 1985;Etherton & Evock, 1986 (Livingston & Moxley, 1982;James et al, 1985), but the mechanism is unknown.…”
Section: Pyruvate Kinasecontrasting
confidence: 45%
“…The differences between rat hepatocytes and sheep adipose tissue in the control of pyruvate kinase activity are in marked contrast with the control of glucose-6-phosphate dehydrogenase, the activity of which is enhanced synergistically in both rat hepatocytes (Kurtz & Wells, 1981) (Vernon & Finley, 1986), pigs (Walton et al, 1986) and cattle (Etherton & Evock, 1986) and in hepatocytes from rats (Amatruda et al, 1983). The effect of glucocorticoids on insulin stimulation of lipogenesis in rat adipose tissue in vitro is not clear, with reports of antagonism (Philipps et al, 1965), synergism (Minshull & Strong, 1985) and no effect (Hallowes et al, 1973), but in vivo they are antagonistic (see Fain, 1979).…”
Section: Pyruvate Kinasementioning
confidence: 99%
“…Unlike the majority of previously reported in vitro studies with primary adipocytes, one recent study with primary porcine adipose cultures described an anti-insulin effect by porcine GH that is similar in many respects to the present 3T3-Ll results [13], such as 1) GH alteration of cellular sensitivity to insulin, and 2) the percent suppression of glucose utilization for lipid synthesis by GH was greater in the presence of insulin than in its absence. However, several significant differences between the two in vitro systems suggest that 3T3-Ll adipocytes may be a more accessible model system to study the mechanism of the anti-insulin effects of GH.…”
Section: Discussionsupporting
confidence: 60%
“…The increased insulin concentration in rbST-treated animals may be due to a compensatory secretion related to a reduced tissue sensitivity to insulin (Walton et al, 1986;Magri et al, 1990). This impairment of insulin action and the consequently reduced glucose uptake by peripheral tissues should facilitate the preferential utilization of glucose by the mammary gland (Ronge and Blum, 1989).…”
Section: Discussionmentioning
confidence: 99%